Scaffolding Preservice Science Teacher Learning of Effective English Learner Instruction: A Principle-Based Lesson Cycle - Roberts, Sarah; Bianchini, Julie A. (Innovations in Science Teacher Education, 2019)
This paper examines a lesson development, implementation, revision, and reflection cycle used to support preservice secondary science teachers in learning to teach English learners (ELs) effectively. We begin with a discussion of our framework for teaching reform-based science to ELs – four principles of effective EL instruction and three levels of language – that shaped both our science methods course, more generally, and the lesson cycle, in particular. We then present a model lesson implemented in the methods course that highlighted these principles and levels for our preservice teachers. Next, we describe how preservice teachers used their participation in and analysis of this model lesson as a starting point to develop their own lessons, engaging in a process of development, implementation, revision, and reflection around our EL principles and language levels. We close with a description of our course innovation, viewed through the lens of the preservice teachers. We attempt to provide practical insight into how other science teacher educators can better support their preservice teachers in effectively teaching ELs.